Influence of Different Professional Prophylactic Methods on Fluorescence Measurements for Detection of Occlusal Caries - Diniz, M. B. [UNESP]; Sciasci, P. [UNESP]; Rodrigues, J. A.; Lussi, A.; Cordeiro, Rita de Cássia Loiola [UNESP] (Karger, 2011)
This study aimed to evaluate the influence of professional prophylactic methods on the DIAGNOdent 2095, DIAGNOdent 2190 and VistaProof performance in detecting occlusal caries. Assessments were performed in 110 permanent teeth at baseline and after bicarbonate jet or prophylactic paste and rinsing. Performance in terms of sensitivity improved after rinsing of the occlusal surfaces when the prophylactic paste was used. However, the sodium bicarbonate jet did not significantly influence the performance of the fluorescence-based methods. It can be concluded that different professional prophylactic methods can significantly influence the performance of fluorescence-based methods for occlusal caries detection. Copyright (C) 2011 S. Karger AG, Basel
Keywords: Caries detection; Fluorescence; Occlusal caries; Permanent teeth; Professional prophylaxis; Prophylactic paste